2022
DOI: 10.3390/rs14030799
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Basal Stem Rot Disease in Oil Palm Tree Using Unmanned Aerial Vehicle-Based Hyperspectral Imaging

Abstract: Early detection of basal stem rot (BSR) disease in oil palm trees is important for the sustainable production of palm oil in the limited land for plantation in Southeast Asia. However, previous studies based on satellite and aircraft hyperspectral remote sensing could not discriminate oil palm trees in the early-stage of the BSR disease from healthy or late-stage trees. In this study, hyperspectral imaging of oil palm trees from an unmanned aerial vehicle (UAV) and machine learning using a random forest algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…These changes can be detected through remote sensing in order to monitor the health of plants and identify areas of water stress [32,40,59,60]. One way to detect water stress in plants is by measuring changes in the reflectance of visible and near-infrared light [40,59,61]. In general, stressed plants will have a lower reflectance in the near-infrared region and a higher reflectance in the visible region [45].…”
Section: General Principlesmentioning
confidence: 99%
“…These changes can be detected through remote sensing in order to monitor the health of plants and identify areas of water stress [32,40,59,60]. One way to detect water stress in plants is by measuring changes in the reflectance of visible and near-infrared light [40,59,61]. In general, stressed plants will have a lower reflectance in the near-infrared region and a higher reflectance in the visible region [45].…”
Section: General Principlesmentioning
confidence: 99%
“… Kurihara et al (2022) used an UAV with hyperspectral imager and used RF machine learning algorithm to classify oil palm disease into various infection severity category. The hyperspectral imager is a sequential two-dimensional imager (Genesia Corp., Tokyo, Japan).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The team was able to calculate the mean reflectance spectra of each segment of the hyperspectral cube of the scene. The results showed that only some spectral bands in the red-edge region could be used adequately to classify BSR infection levels ( Kurihara et al, 2022 ). This was also explained by Horler, Dockray & Barber (1983) , where the red-edge region were tightly linked to the light absorption by the chlorophylls on the plant cells.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the past 20 years the technology of unmanned aerial vehicle (UAV) has been applied to a number of studies in various fields, including environment, forestry and ecosystem, and wildfire effect. For agriculture, UAVs have been used to develop the precision agriculture (Akhtman, et al, 2017;Tsouros et al, 2019;Zheng, et al, 2021;Velusamy, et al, 2022) and analyze crop health (Izzuddin et al, 2020;Kurihara et al, 2022).…”
Section: Introductionmentioning
confidence: 99%